Unpacked : a history of Caribbean tourism - Scott, Blake C., 1983- (Histories and cultures of tourism., 2022)
"Explains the historical roots of Caribbean tourism and follows a well-traveled sea route linking the U.S. east coast with the island of Cuba and the Isthmus of Panama to describe how the history of U.S. imperialism became the heart of the region's modern tourism industry"--